Diversidad de escolítidos en plantaciones de Tectona grandis L. f. (teca) en la Provincia del Guayas, año 2018. - Montiel Plaza, Jenifer Stefania (2018)
present research project was carried out in the sites of La Mont, Santa Rosa and La Valentina, located in the Balzar canton. The objectives of this study were to identify and determine the diversity of the scolitids associated with teak plantations. 36 intersecting flight traps were placed at a height of 1.30 m, at ground level, the traps were primed with alcohol (96%) and distilled water. The collection of insects was made every 8 days, during the months of August, September and October, a total of 9560 insects were collected, of which 5064 individuals in Santa Rosa, 2672 individuals in La Mont and 1824 in La Valentina. The total of scolitids are grouped in 9 species, being the most abundant species Hypothenemus sp., Xyleborus affinis, Premnobius cavipennis, Xyleborus volvulus. The weeks in which the highest number of scolitids was collected were, in the seventh, fourth and seventh week, in the sites La Mont, Santa Rosa and La Valentina respectively. In Santa